SOCIO-ECONOMIC EFFECTS OF HUSBANDS’ MIGRATION ON SPOUSES AND CHILDREN IN KUMBOTSO LOCAL GOVERNMENT AREA OF KANO STATE - Abdurraheem, Anifat; Galadima, Abdullahi; Veronica, Viashima (African Journal of Social and Behavioural Sciences, 2025)
Husbands’ migration is a major concern in Kumbotso LGA of Kano State. This cemented the core thrust of the research as it dwells on assessing the impact of husbands’ migration on spouses and children in Kumbotso LGA of Kano State, Nigeria. The objective of this study includes examining husbands’ migration, examining the effect of husbands’ migration on spouses and children and finding ways to mitigate the problem (s) of husbands’ migration. The study employed Everett Lee’s (1966) model of migration as the foundation for explaining the relationships between core variables. A total of 166 respondents were sampled for the study, with 150 used for the quantitative survey and 16 used as Key informants. Descriptive statistics were used to analyse the data, and the results were presented in the form of tables. The results generated showed that the causes of the husband’s migration were poor earnings, unfavourable government policies, and a high rate of unemployment. The impact of this migration includes eroded family structure and relationships, women’s engrossment in more responsibilities and a test on their decision-making capacity, delinquent behaviour, and drug trafficking by children. The findings concluded that there are negative impacts of husbands’ migration on spouses and children. The study recommended that the Kano State Government should promote financial stability, education and employment opportunities; reduce the drivers of migration and promote resilience, thereby enabling husbands to stay rather than migrate.